THE INQUIRY OF LOCAL CULTURE AS LEARNING MODEL OF INDONESIAN PEOPLE AND CULTURE SUBJECT TO IMPROVE STUDENT’S CREATIVITY - Maaliah, Eda; Permatasari, Ita; Widodo, Yulius Harry; Aziz, Muhyiddin (Humaniora Scientia, 2019)
To compare differences in students learning outcomes and creativity about local culture before and after the application of the inquiry model of local culture, and as an evaluation of learning process related to subject namely Indonesian People and Culture are the aims of this study. This research was conducted in the fourth semester students of English Study Program consisting of 56 students. This action research had two cycles. Each consisted of planning, acting, observing, and reflecting. In this research the researcher employed qualitative and quantitative data analysis. Based on the research findings from teaching-learning process, the researcher can draw some final conclusions. The students’ response was very good after implementing inquiry learning model. The students were active in giving answer of each question. It was also shown from the improvement of the mean scores in every cycle as follows : in pre-test was 60, in the first cycle was 70, and in the second cycle was 85. Additionally, there were 50 of 56 students who got point up 75 in the second cycle, it means it was 90 %. Based on the finding, the alternative hypothesis stating that inquiry learning model can improve the students’ creativity of local culture. Keywords: Inquiry Model, Local Culture, Indonesian People and Culture, Students’ Creativity